Morphology and Properties of Polyester/Exfoliated Graphite Nanocomposites - Kim, Hyunwoo; Macosko, Christopher W (Macromolecules, 2008)
Nanocomposites reinforced with graphite platelets were compared to those with functionalized graphite sheets (FGS) prepared by partial pyrolysis of graphite oxide. Melt dispersion in poly(ethylene-2,6-naphthalate) (PEN) was quantified using a range of characterization techniques: electron microscopy, X-ray scattering, melt rheology, electrical conductivity, gas barrier, and mechanical properties. Conductivity percolation was obtained with as little as 0.3 vol % FGS, whereas 3 vol % was required for graphite. The threshold concentrations of FGS and graphite for rigidity percolation determined with melt rheology were in good agreement with conductivity percolation. Hydrogen permeability of PEN with 4 wt % FGS was decreased by 60% while the same amount of graphite reduced permeability only 25%. Structural differences between graphite and FGS were characterized with atomic force microscopy (AFM), Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS). The highly exfoliated morphology of FGS was maintained in the composites as revealed by electron microscopy and X-ray scattering while graphite layers remained stacked together even after melt processing. Even though the tensile stiffness and dimensional stability of PEN were improved, the extent of reinforcement with FGS for these two properties was not as significant. This was attributed to the wrinkled structure of FGS and atomistic defects.